A study on the Impact of Tesla’s Autonomous Driving Technology on Its Performance - Zhang, Rui; Ding, Xilu (International Journal of Global Economics and Management, 2024)
With the rapid development of the automobile industry, autonomous driving technology has become an important research and development direction for major automobile manufacturers. As a leader in electric vehicles and autonomous driving technology, Tesla's development of autonomous driving technology has had a significant impact on the company's performance. This article explores the strategic significance and competitive advantages of autonomous driving technology to Tesla by analyzing the development history of Tesla's autonomous driving technology, its technical characteristics and its impact on the company's performance.